Institutional reform for innovation and entrepreneurship: An agenda for Europe - Niklas Elert; Magnus Henrekson; Mikael Stenkula (Research Institute of Industrial Economics (IFN), 2017)
It is imperative that the economies of the European Union become more entrepreneurial to promote innovation and economic growth. To achieve these goals, we propose a reform strategy with respect to (i) the rule of law and the protection of property rights; (ii) the tax system; (iii) regulations governing savings, capital and finance; (iv) the organization of labor markets and social insurance systems; (v) regulations governing goods and service markets; (vi) regulations governing bankruptcy and insolvency; (vii) R&D, commercialization and knowledge spillovers; (viii) human capital investments; and (ix) informal institutions. Overall, the proposed institutional changes move in a liberalizing direction; however, one-size-fits-all policy reforms aimed at freer markets will not necessarily be successful. Instead, a successful reform strategy must consider country differences that affect the viability of reform without abandoning the long-term goal of institutional liberalization to promote entrepreneurship, innovation and growth.
Keywords: L26; L5; M13; O31; P14; 330; Entrepreneurship; European Union; Innovation; Institutions; Policy reform; Regulation; Self-employment; Technologiepolitik; Entrepreneurship; Unternehmensgründung; Innovation; Institutioneller Wandel; Gründungsförderung; Selbstständige; EU-Staaten